An Interface‐Controlled Redox Switch for Wastewater Remediation. Issue 2 (21st November 2017) - Khaire, Siddhi; Gaikwad, Pramod; Aralekallu, Shambhulinga; Bhat, Zahid Manzoor; Kottaichamy, Alagar Raja; Devendrachari, Mruthyunjayachari Chattanahalli; Thimmappa, Ravikumar; Shafi, Shahid Pottachola; Gautam, Manu; Thotiyl, Musthafa Ottakam
Abstract: Bipolar junction transistors (BJTs) can function as electrically reversible switches; nevertheless, triggering such circuits requires a distinct voltage bias at the base terminal. Here, we show a proof‐of‐concept of an electrochemical switching device equipped with a redox electrode whose bi‐stable interfacial chemistry, reliant on hydronium ion strength, can provide distinct logic HIGH (1) and logic LOW (0) levels of operation, enabling it to control and command an electronic circuit without the aid of any external voltage input. Electrochemical impedance spectroscopy, quartz crystal microbalance studies, and UV/Vis spectroscopy demonstrate that discrete logic levels are controlled by the solvent‐mediated charge injection/ejection kinetics at the redox‐active half‐cell electrode, leading to a chemically reversible switch with a response time of approximately 1 s and an operating speed of 225 cycles per hour. We demonstrate that the logic HIGH level of the interfacial twin states is actuated when exposed to acid‐contaminated wastewater, automatically triggering the command for remediation. Abstract : Waterworks : An interface‐controlled command control chemical switch for wastewater treatment.